Experimental and numerical investigations on uniaxial-stress ductility failure of additive manufactured lattice structures based on frequency fatigue technique - Onyibo, Emmanuel Chukwueloka; Gazioglu, Aysegul; Ahmed, Abdullah A. M.; Ameer, Ahmed Ameer Adil; Abdelrahman, Mazin E. B.; Oladipupo, Omogbolahan Adedamola; Safaei, Babak (Springer Wien, 2025)
In this study, frequency-based fatigue failure of strut-based lattice-type structures was investigated. In this regard, firstly, experiments and numerical approaches were employed in the exploration of the mechanical characteristics of lattice-type samples under uniaxial compressive forces to analyze their dynamic failure responses. The frequency-based fatigue failure life of different lattice structures with the same volume fraction were analyzed and some strut modifications were made to increase the reliability of the lattice structure. Harmonic analysis was employed to calculate fatigue life using stress-life technique. Then, the samples were 3D printed by creating specimens with different structures while maintaining consistent mass, and unit cell size. Stresses of lattice structures were observed experimentally and validated numerically by using finite element analysis (FEA). Experimental data were compared with those obtained from ANSYS material designer simulations for their linear elasticity. Then, compressive strength and stiffness were taken from the experimental data. Remarkably, among all 3 specimens, octet structure had a good dynamic behavior and tended to resonate at much higher frequencies than the other samples. Also, in terms of compressive strength, cubic structure had the highest value. Overall, lattice structure mechanical behaviors were observed considering fatigue damage life for single frequency scenarios and monitoring time until failure.
Keywords: Performance; Design